Frequency and associated factors of structural progression of open-angle glaucoma in the Beijing Eye Study - Wang, Ya Xing; Jonas, Jost B.; Xu, Liang (British journal of ophthalmology, 2012)
Background To examine factors associated with progression of open-angle glaucoma in a population-based setting. - Methods The population-based Beijing Eye Study, which included 4439 subjects with an age of 40+ years in the year 2001, was repeated in 2006. Optic disc photographs of the baseline examination versus follow-up examination were compared. - Results Out of 111 open-angle glaucoma patients examined in 2001, 77 (69%) subjects participated in the follow-up examination and 16 (21%) eyes showed glaucoma progression. Glaucoma progression was associated with smaller rim area (p=0.001), larger β zone (p=0.037), higher frequency of β zone increase during follow-up (p=0.01), higher prevalence of disc haemorrhages (p=0.01) and higher single intraocular pressure (p=0.04). In multiple regression analysis, only smaller rim area remained significantly associated with glaucoma progression. Glaucoma progression was not associated with optic disc size (p=0.70), mean blood pressure (p=0.43), ocular perfusion pressure (p=0.96), retinal vessel diameter and retinal microvascular abnormalities (all p>0.10), prevalence of diabetes mellitus (p=0.75) and arterial hypertension (p=0.26), prevalence of dyslipidaemia (p=0.28), refractive error (p=0.69), and central corneal thickness (p=0.97). - Conclusions In a population-based setting in adult Chinese, factors showing an association with open-angle glaucoma progression were an advanced stage of the disease (ie, small rim), presence of disc haemorrhages, larger area of β zone and higher frequency of β zone increase, and higher intraocular pressure. Glaucoma progression was not significantly associated with optic disc size, central corneal thickness, retinal vessel diameter and retinal microvascular abnormalities, and systemic diseases such as diabetes mellitus and arterial hypertension.
Gesehen am 21.02.2019